La necesidad de expedir una ley reformatoria al código del trabajo ecuatoriano, en relación al tiempo de negociación del contrato colectivo para que se apruebe por el ministerio de la ley - Lopez Diaz, Edwin Hermógenes (2014)
In our country, in in full force of the Constitution of the Republic of Ecuador, collective agreements last much longer in negotiation and the compulsory process to submit to the Court of conciliation and arbitration, so it is necessary that reform of the labour code so that it has not approved the collective agreement in the course of six months since presents the draft collective contract. Addition in article 224 of the Labour Code stipulated on the negotiation of the collective agreement, will be given within fifteen days of such notification, the parties must initiate the negotiation that will be completed within a maximum of thirty days, unless they jointly inform the labour inspector the need for a further specified period to conclude the negotiation. Hence, it is necessary to make or propose a reform legal aims to overcome this problem, is to say that workers can sign the collective agreement in the shortest possible time and not have to give so many long to your collective matter.